Det landmilitære forsvar af den sjællandske øgruppe og Bornholm under den kolde krigs sidste to årtier (1970’erne og 1980’erne) Del I: Perioden fra ca. 1970 til 1979 - Rasmussen, Peter Hertel (Fra Krig og Fred, 2026)
The military defence of the Zealand group of islands and Bornholm in the 1970s This article is the first of two articles, analyzing the Danish defence of the eastern part of Denmark, that is the Zealand group of islands and Bornholm, during the last two decades of the cold war. A second article on the developments in the 1980s up to the fall of the Berlin wall is scheduled to appear in a later issue of this magazine. A brief summary of the defence of the Zealand group of islands would highlight the numerical discrepancy between on the one hand the Danish forces available for the defence of this part of Denmark, combined with possible British reinforcements. And on the other hand the continuing build-up of both the military and naval forces of the Warsaw Pact countries (the Soviet Union, Poland and East Germany) in the Baltic. The Danish strategy was concentrated on establishing a limited number of solid coastal defences in areas along the east coast of Zealand, considered most suitable for amphibious landings. While the main brunt of resisting an invasion would be borne by coastal defence batalions, the two Danish armoured infantry brigades, stationed in Zealand, would conduct immediate counterattacks against those Warsaw Pact forces who succeeded in establishing bridgeheads. The timespan for conducting a succesful defence against an invasion force was considered to be very short, a few days at the most. While seaborne landings were considered the most likely way of conducting an invasion of Zealand, the build-up of Warsaw Pact airborne forces (including the introduction of the BMP infantry combat vehicle) over the decade led to a fundamental rethinking of the Danish strategic concept. While the basic element in this rethinking, that is the immediate encapsulation of Warsaw Pact airborne forces with a view of destroying them, the tactics and organization of doing so would be left to the following decade to decide.